Assessment of dental anodontia among Ferdinand I Military Technical Academy students in Romania: Dental anomalies among military students - Dumitrița Dan, Ancuța; Lucia Ghergic, Doina (Vojnosanitetski pregled, 2022)
Background/Aim. Data regarding tooth absence among Romanian military personnel are lacking. The aim of this study was to determine the prevalence of dental anomalies among military students at the Military Technical Academy in Bucharest, Romania. Methods. A cohort of 318 military students was enrolled in the study. Each participant unde-rwent an extensive evaluation of their oro-dental health status based on guidelines of the European Global Oral Health Indicators Development II Project (EGOHID II). Results. Anodontia was discovered in 6 participants (prevalence rate was 1.9%), namely 4 women (prevalence among women was 4.6%) and 2 men (prevalence among men was 0.87%). Five of the six patients had never been previously diagnosed with anodontia. The most commonly affected teeth were second premolars (n = 8), followed by first premolars (n = 4) and second permanent molars (n = 2). Premolar anodontia was equally common in the maxilla and the mandible; both instances of molar anodontia were in the mandible. None of the participants with anodontia had remaining temporary teeth. A brief overview and two cases of dia-gnosed patients, who presented with inferior bilateral second molar anodontia and quadruple canine inclusion and a quadruple second premolar anodontia, are given. Conclusion. Military students in Romania would benefit from systematic dental evaluation and long-term monitoring prior to enrollment in the Military Academy.